2008
DOI: 10.1590/s1982-56762008000500007
|View full text |Cite
|
Sign up to set email alerts
|

First report of Diaporthe phaseolorum var. caulivora infecting soybean plants in Brazil

Abstract: In March 2006, diseased soybean plants (Glycine max) were found in the municipalities of Passo Fundo and Coxilha, state of Rio Grande do Sul, Brazil, showing withered, brown leaves and light to reddish-brown discoloration and necrosis (canker) of the lower half of the stem. Cultural characteristics in potato dextrose agar showed identical patterns to those described for Diaporthe phaseolorum var. caulivora (Dpc). The rDNA-ITS sequence data from the Brazilian strain CH 40/06 (GenBank accession number EU622854) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Distribution -South Africa ). Distribution -South Africa (Vrandečić et al 2005), Glycine max (Pioli et al 2001, Bradley & Li 2006, Costamilan et al 2008, Grijalba & Ridao 2012, Sun et al 2012, Chiesa et al 2013, Cummings & Bergstrom 2015, Vigna sp. (Sato et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution -South Africa ). Distribution -South Africa (Vrandečić et al 2005), Glycine max (Pioli et al 2001, Bradley & Li 2006, Costamilan et al 2008, Grijalba & Ridao 2012, Sun et al 2012, Chiesa et al 2013, Cummings & Bergstrom 2015, Vigna sp. (Sato et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…(Sato et al 2014). Distribution -Argentina (Pioli et al 2001, Grijalba Ridao 2012, Chiesa et al 2013, Brazil (Costamilan et al 2008), Canada (Ginns 1986), Croatia (Vrandečić et al 2005), Italy (Zhang et al 1997), Japan (Sato et al 2014), Korea (Sun et al 2012), USA (Bradley & Li 2006, Cummings & Bergstrom 2015 for illustrations and descriptions of asexual morph. Type -Australia, Queensland, Gatton, from stem of Rapistrum rugosum (Brassicaceae), 24 Nov. 2011, S.M.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Diaporthe phaseolorum var. caulivora, which was isolated from the soybean in this study, is an important pathogen in North and South America (Kulik, 1989;Hartman et al, 1999;Costamilan et al, 2008), but has never been found in Japan. Such infested grains imply risks; not only in bean sprout production but also in crop protection of the importing countries.…”
Section: Discussionmentioning
confidence: 60%
“…Instead, programmed cell death or apoptosis occurs in the mycelial cells that are in contact with an isolate representing different vegetative compatible groups (Leslie, 1993). Previous vegetative compatibility assays have been performed for the SSC pathogens, but involving solely two Brazilian isolates (Costamilan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%